2003
DOI: 10.1002/hed.10215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation on vestibular evoked myogenic potentials in nasopharyngeal carcinoma survivors

Abstract: Delayed VEMPs in NPC survivors are possibly due to radiation-induced otitis media, a brainstem lesion, or neck fibrosis. Hence, VEMP testing may expand the test battery for clinicians to explore balance problems in NPC survivors after irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…64 In survivors of irradiated nasopharyngeal carcinoma, p13 and n23 latencies were delayed in 50% of the ears in subjects irradiated once and 100% of the ears in those irradiated twice. 70 These abnormalities were attributed to brainstem pathology.…”
Section: Vemps Evoked By Galvanic Stimulationmentioning
confidence: 98%
“…64 In survivors of irradiated nasopharyngeal carcinoma, p13 and n23 latencies were delayed in 50% of the ears in subjects irradiated once and 100% of the ears in those irradiated twice. 70 These abnormalities were attributed to brainstem pathology.…”
Section: Vemps Evoked By Galvanic Stimulationmentioning
confidence: 98%
“…In 12 patients undergoing VEMP test, excluding one patient aged > 60 years, percentages of abnormal VEMPs remained the same (Table ). Although cVEMP test was not performed in NPC patients prior to irradiation, our previous study reported that normal cVEMPs were identified in fresh NPC patients, which further supports that abnormal cVEMPs in NPC survivors are unrelated to NPC itself but irradiation.…”
Section: Discussionmentioning
confidence: 56%
“…Absence of VEMPs has been, in addition, reported in 19Á25% of sides tested [10]. A prolongation of VEMPs was also shown in large vestibular schwannomas compressing the brainstem [9] and in survivors of nasopharyngeal carcinoma after irradiation [11].…”
Section: Discussionmentioning
confidence: 95%